POLEMIK CATRA PADA STUPA INDUK CANDI BOROBUDUR: KAJIAN ARKEOLOGI DAN FILOSOFIS - LEE, So Tju Shinta; LEE, Salim (Paradigma: Jurnal Kajian Budaya, 2025)
This paper explores the profound meaning of the main stupa at Candi Borobudur and analyzes the implications of the proposed catra installation on the monument’s spiritual and cultural values. The interpretation is based on a post-processual perspective that emphasizes the importance of considering context, internal evidence, and internal symbolic relationships rather than seeking externally sourced validation. Through a combination of literature study, observation, and comparative analysis of stupas at Borobudur itself, contemporary Buddhist candis in Central Java, and various types of stupas abroad, this research concludes that the proposal for catra installation on the main stupa of Borobudur lacks a strong foundation both archaeologically and philosophically and does not contribute to the appreciation of spiritual values. The main stupa represents the pinnacle of the highest spiritual realization: the Buddha’s awakened mind (Dharmakaya). This ultimate meaning transcends other conventional symbolisms. This study underscores the importance of a contextual and comprehensive understanding of Borobudur, encompassing cultural, spiritual, and preservation aspects. This, in turn, has implications for the effectiveness of interpretation, conservation, and more sustainable development strategies for Borobudur and other Buddhist candi sites.